PERANAN AZIS ASYARIE DALAM PENGEMBANGAN PENCAK SILAT (MAENPO) ALIRAN CIKALONG DI KABUPATEN CIANJUR (1980-2017) - Muhammad Salman Syamsuri, Salman (2023)
This research is motivated by the current phenomenon in the development of Maenpo Cikalong Pencak Silat in Cianjur Regency. Among the many martial arts, Maenpo is not the preferred choice for the younger generation. The reason is, Maenpo is one of the world heritages that has been established by UNESCO. Developing Maenpo is important to provide education to the younger generation about the uniqueness of Maenpo and to further improve its development. The author's interest in the unique Pencak Silat Maenpo martial art and the need for more attention from society led to the study of this topic. This thesis aims to analyze the The Role Of Aziz Asyarie In The Development of Maenpo Cikalong Pencak Silat in Cianjur Regency from 1980 to 2017. The research method used in this study is historical research, which includes four steps: heuristics, criticism, interpretation, and historiography. The results of this thesis research found several findings, including the background of Aziz Asyarie's life as a developer of Maenpo Pencak Silat and his success in getting Maenpo listed in UNESCO, along with the efforts of the West Java Provincial Government. Aziz Asyarie is a maestro of Maenpo Cikalong style martial arts in Cianjur Regency, and he was one of the students of the creator of Maenpo Cikalong style, R.H. Ibrahim Djajaperbata. Another finding is the significant role played by Aziz Asyarie in developing Pencak Silat Maenpo. Furthermore, the study found the efforts made by Aziz Asyarie in developing Maenpo Pencak Silat, as well as the obstacles and challenges faced in developing Maenpo.